The First Record of Two Species of Protozoa: Vorticella globulariaMüller, 1773 and Vorticella costata(Sommer, 1951)fromPlaniliza abu in the Babylon Province, Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
During the period from November 2015 till the end of March 2016, a total of 218 fish specimens belonging to Planiliza abu   from Euphrates River at Al-Hilla city  and the Babil drainage networkBabylon province were inspected for parasites at Laboratory at the Al-Musaib Technical College. Two Vorticella were recorded for the first time in Iraq from skin and gills of P. abu. These were:Vorticella globulariaMüller, 1773 and  Vorticella costata(Sommer, 1951). The description and measurement of this parasite as well as their measurements  were given